FRACTURE RESISTANCE OF MANDIBULAR FIRST MOLAR REINFORCED WITH DIFFERENT POST DESIGNS AND CORE PREPARATION AFTER OBTURATION –AN IN VITRO STUDY - Dr. Puja Khakal; Dr. Rajendra Daule; Dr. Bhavna Gaikwad; Dr. Rohini Mahajan; Dr. Saurabh Lonare; Dr Manjunath S Hemagiriyappa (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Aim: This study aim to compare fracture resistance of mandibular first molar reinforced with horizontal diagonal fibre post and vertical metal post and core preparation after obturation Materials and methods: Twenty –four extracted mandibular first molar teeth were selected, divided into four groups (GP) - GP I (endodontically treated-no post)), GP II (horizontal diagonal post design –fibre post), GP III (vertical post – metal). The individual teeth were mounted on acrylic bases and tested under universal testing machine for fracture resistance. Results : Group II (horizontal diagonal fibre post) design had higher fracture resistance as compared to the vertical metal post design and no post design and core preparation . Conclusion : Within the limitations of this study, it can be concluded that horizontal diagonal fibre post design has better fracture resistance as compared to vertical metal post